Primi dati sul comportamento alimentare dell’Averla maggiore, Lanius excubitor, svernante in provincia di Vicenza - FIORETTO M.; PEGORARO F.; BONATO, LUCIO (1998)
Preliminary dara on hunting techniques and prey species of Great Grey Shrike Lanius excubitor, wintering in the province ofVicenza, were collected during the winter of 1995-96.